2017
DOI: 10.1039/c7mb00181a
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomic profiling and biochemical evaluation of the follicular fluid of endometriosis patients

Abstract: Diseases are complex systems that can be studied through the integration of data derived from different disciplines to obtain a global and reliable picture of the biological phenomenon under investigation. Based on the recent observations that the metabolomics profiling of follicular fluids reflects the ovarian microenvironment of women and that endometriosis represents an example of complex diseases, clearly diagnosed by laparoscopy, we thought that the follicular fluids of endometriosis patients can represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 24 publications
4
50
0
Order By: Relevance
“…Metabolites not only represent the final products of biological regulatory processes but also act as communicators between the information-rich genome and the functional phenotype. In the past few years, several studies identified a list of potential diagnostic candidates in peritoneal fluid, blood and urine from endometriosis patients at different stages of disease and menstrual cycle [ 9 , 10 ]. However, potential biomarkers from the eutopic endometrium remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites not only represent the final products of biological regulatory processes but also act as communicators between the information-rich genome and the functional phenotype. In the past few years, several studies identified a list of potential diagnostic candidates in peritoneal fluid, blood and urine from endometriosis patients at different stages of disease and menstrual cycle [ 9 , 10 ]. However, potential biomarkers from the eutopic endometrium remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other chemokines such as CXCL1, CXCL2, CXCL3, and G-CSF can also attract neutrophils [28]. Consistently, patients with endometriosis displayed a significant higher production of CXCL1, CXCL2, and CXCL8 in the peritoneal fluid as compared to those from controls [29][30][31]. Secretion of CXCL8 is significantly higher in the eutopic endometrial stromal cells from women with endometriosis than that in the control [32].…”
Section: Discussionmentioning
confidence: 68%
“…Endometriosis could also affect the metabolic processes, thereby altering the microenvironment of the follicle and the oocyte development. Indeed, metabolomic signatures related to endometriosis have been identified in the follicular fluid [36][37][38], and in other biological fluids [39,40], despite some reports suggesting the opposite [41]. One study reported that the follicular fluid of infertile women with endometriosis could impair nuclear maturation and promote meiotic anomalies in bovine oocytes matured in vitro [42].…”
Section: Discussionmentioning
confidence: 99%